2019
DOI: 10.1111/ijfs.14153
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction and in vitro simulated gastrointestinal digestion of phenolic compounds from purple sweet potato

Abstract: Summary The total content of phenolic compounds in purple sweet potato (PSP) was determined and the release of such compounds from PSP in gastrointestinal digestion was studied in vitro. The extraction conditions for the maximum recovery of free phenol (FP) and bound phenol (BP) from PSP were determined by response surface methodology (RSM). The maximum recovery of FPPSP was 14.16 ± 0.87 mg GAE per g short for dry weight (DW), which was obtained using 60% (v/v) ethanol maceration with a liquid–solid ratio of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Purple sweet potatoes are known to be an excellent source of phenolic compounds that act as antioxidants. According to the root size classification applied in this work, PSP-L was found to have TPC levels comparable with those reported by Meng et al [ 19 ] and Wang et al [ 20 ] who determined the maximum phenolic concentration at 14.16 and 15.25 mg TPC/g DW (in S-3 variety), respectively. Interestingly, Mexican variety PSP-S not only had higher TPC than the values previously reported [ 21 ], but also it exceeded phenolic content of other edible roots and tubers, such as purple carrots (3.94 mg/g DW), Vitelotte-variety of purple potatoes (8.45 mg/g DW) [ 22 ], and P-3 variety of purple potatoes (10.02 mg TPC/g DW) [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Purple sweet potatoes are known to be an excellent source of phenolic compounds that act as antioxidants. According to the root size classification applied in this work, PSP-L was found to have TPC levels comparable with those reported by Meng et al [ 19 ] and Wang et al [ 20 ] who determined the maximum phenolic concentration at 14.16 and 15.25 mg TPC/g DW (in S-3 variety), respectively. Interestingly, Mexican variety PSP-S not only had higher TPC than the values previously reported [ 21 ], but also it exceeded phenolic content of other edible roots and tubers, such as purple carrots (3.94 mg/g DW), Vitelotte-variety of purple potatoes (8.45 mg/g DW) [ 22 ], and P-3 variety of purple potatoes (10.02 mg TPC/g DW) [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Su et al (2019) have concluded that when phenolic compounds such as ellagitannins were exposed to gastric and intestinal pH environments, the ester bonds were hydrolysed to release mainly ellagic and gallic acid compounds with antioxidant capacity. Meanwhile, under the activation of enzymes, bound phenolics is hydrolysed from macromolecular compounds to free phenolics, and thus, the phenolic content in the system increases (Meng et al, 2019). For instance, pancreatin can degrade complex phenolics into smaller units (Corona et al, 2017).…”
Section: Determination Of Frapmentioning
confidence: 99%
“…In China, the most popular varieties of sweet potato are purple and orange‐fleshed due to their excellent color and nutritional characteristics. Orange‐fleshed sweet potato rich in carotenoids that show strong antioxidant capacities due to conjugated double bonds (Azeem et al., 2020; Kourouma et al., 2020; Mordi et al., 2020), while purple‐fleshed sweet potato possesses an abundant amount of phenolics compounds as compared to other colored ones (Meng et al., 2019; Wang et al., 2018), in which anthocyanins are more stable than those from other plants (Quan et al., 2019), showing the immense potential of free radical scavenging, anti‐inflammatory, and anticarcinogenic activities (Salehi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%